Prevention of Pesticide Toxicity Risk through the Farmer Community Movement to Resolve Toxicity - Mahyuni, Eka Lestari; Harahap, R. Hamdani; Harahap, Urip; Nurmaini (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Pesticide toxicity is a phenomenon that needs to be prevented, which is generally caused by the risky behavior of using pesticides. This PPM activity is one of the community empowerment activities to reduce the risk of pesticide toxicity through the GEMPAR (Gerakan Masyarakat Petani Atasi Racun) action. GEMPAR consists of eight farmer movements to prevent the risk of toxicity due to pesticides used. The eight GEMPAR actions were applied by farmers with promotional and educational methods through the GEMPAR demonstration activities. The demonstration implementation method is presented by the farming community which is divided into three areas in Sumber Mufakat Village, namely Berhala, Simpang Sumbul, and Pasar Sumbul. Demonstrations from these three areas were contested as a form of appreciation for the community so that they could motivate the community to participate in preventing the risk of pesticide toxicity. The demonstration that displayed the messages of the eight GEMPAR movements was carried out well. Each demonstration gives special characteristics either through songs or slogans related to preventing the risk of toxicity. The community became very enthusiastic about the demonstration which could increase the participation of the farming community to use better and healthier pesticides sustainably.